Current perspectives and trends in the treatment of brain arteriovenous malformations: a review and bibliometric analysis - Tang, Weixia; Chen, Yang; Ma, Li; Chen, Yu; Yang, Biao; Li, Ren; Li, Ziao; Wu, Yongqiang; Wang, Xiaogang; Guo, Xiaolong; Zhang, Wenju; Chen, Xiaolin; et al. (Frontiers in Neurology, 2024)
Background Currently, there is a lack of intuitive analysis regarding the development trend, main authors, and research hotspots in the field of cerebral arteriovenous malformation treatment, as well as a detailed elaboration of possible research hotspots. Methods A bibliometric analysis was conducted on data retrieved from the Web of Science core collection database between 2000 and 2022. The analysis was performed using R, VOSviewer, CiteSpace software, and an online bibliometric platform. Results A total of 1,356 articles were collected, and the number of publications has increased over time. The United States and the University of Pittsburgh are the most prolific countries and institutions in the field. The top three cited authors are Kondziolka D, Sheehan JP, and Lunsford LD. The Journal of Neurosurgery and Neurosurgery are two of the most influential journals in the field of brain arteriovenous malformation treatment research, with higher H-index, total citations, and number of publications. Furthermore, the analysis of keywords indicates that “aruba trial,” “randomised trial,” “microsurgery,” “onyx embolization,” and “Spetzler-Martin grade” may become research focal points. Additionally, this paper discusses the current research status, existing issues, and potential future research directions for the treatment of brain arteriovenous malformations. Conclusion This bibliometric study comprehensively analyses the publication trend of cerebral arteriovenous malformation treatment in the past 20 years. It covers the trend of international cooperation, publications, and research hotspots. This information provides an important reference for scholars to further study cerebral arteriovenous malformation.